Salinity effect on embryonic development and survival of the first zoeal stage of Macrobrachium tenellum (Smith, 1871) (Crustacea, Palaemonidae) - Vargas Ceballos, Manuel A. (2018)
The objective of this work is to provide information to understand the effect of different salinities on the survival of embryos and newly-hatched larvae of Macrobrachium tenellum. The survival of M. tenellum embryos was similar in all treatments up to nine days with an average of 94%. At day 12, survival was higher at the lower salinities (90 and 80% at 10 and 0 psu, respectively), whereas total mortality was observed at 30 psu. There were no significant differences in treatments 10 and 0 psu. The treatment that showed the higher hatching percentage was 10 psu (82%); hatching at 0 and 20 psu treatments were 60 and 55%, respectively. Larvae kept at 10 psu showed higher survival 7 days after hatching (98%), meanwhile, larvae maintained in freshwater (0 psu) failed to survive beyond the fifth day (keeping the larvae without food). According to the results obtained in this research, embryonic development of M. tenellun can develop between 0 and 10 psu, whereas, optimal salinity for hatching and development of first larval stages are between 10 and 9 psu.